Real-World Effectiveness and Safety of Eculizumab in AQP4-IgG Positive Neuromyelitis Optica Spectrum Disorder: A Multicenter Observational Study - Koc, Emine Rabia; Yetkin, Mehmet Fatih; Saridas, Furkan; Turan, Omer Faruk; Sevim, Serhan; Terzi, Murat; Siva, Aksel (Sage Publications Ltd, 2025)
[Abstract Not Available]
41st Congress of the European-Committee-for-Treatment-and-Research-in-Multiple-Sclerosis (ECTRIMS) -- SEP 24-26, 2025 -- Barcelona, SPAIN